Aluminum Oxide at the Monolayer Limit via Oxidant‐Free Plasma‐Assisted Atomic Layer Deposition on GaN. (12th June 2021) - Henning, Alex; Bartl, Johannes D.; Zeidler, Andreas; Qian, Simon; Bienek, Oliver; Jiang, Chang‐Ming; Paulus, Claudia; Rieger, Bernhard; Stutzmann, Martin; Sharp, Ian D.
Abstract: Atomic layer deposition (ALD) is an essential tool in semiconductor device fabrication that allows the growth of ultrathin and conformal films to precisely form heterostructures and tune interface properties. The self‐limiting nature of the chemical reactions during ALD provides excellent control over the layer thickness. However, in contrast to idealized growth models, it is challenging to create continuous monolayers by ALD because surface inhomogeneities and precursor steric interactions result in island growth. Thus, the ability to create closed monolayers by ALD would offer new opportunities for controlling interfacial charge and mass transport in semiconductor devices, as well as for tailoring surface chemistry. Here, encapsulation of c‐plane gallium nitride (GaN) with ultimately thin (≈3 Å) aluminum oxide (AlO x ) is reported, which is enabled by the partial conversion of the GaN surface oxide into AlO x using sequential exposure to trimethylaluminum (TMA) and hydrogen plasma. Introduction of monolayer AlO x decreases the work function and enhances reactivity with phosphonic acids under standard conditions, which results in self‐assembled monolayers with densities approaching the theoretical limit. Given the high reactivity of TMA with surface oxides, the presented approach likely can be extended to other dielectrics and III–V‐based semiconductors, with relevance for applications in optoelectronics, chemical sensing, and (photo)electrocatalysis. Abstract : Atomic layer deposition (ALD) is a key technique for developing and producing nanoelectronic devices. The name "atomic layer deposition" suggests layer‐by‐layer growth of atomically thin films. However, in practice, 3D growth occurs owing to incomplete surface coverage within each cycle. This work addresses this challenge and demonstrates self‐saturating growth of a continuous aluminum oxide monolayer by oxidant‐free plasma‐assisted ALD.